The Impact of Generative Artificial Intelligence on the Protection of Data Legal Interests in Criminal Law: A Case Study of ChatGPT - Xu, Yuanhao (Transactions on Social Science, Education and Humanities Research, 2025)
The rapid advancement of generative artificial intelligence (GAI) poses significant challenges to the current framework of data legal interest protection under Chinese criminal law. Represented by models such as ChatGPT, GAI systems possess powerful capabilities in data extraction, analysis, and generation. Even when data is obtained legally, the use of deep mining, correlation analysis, and multimodal outputs may give rise to new forms of data-related criminal risks. However, China’s current criminal law framework, which centers on “data control” and emphasizes the protection of data at the source, lacks adequate regulation over behaviors characterized by “lawful acquisition + unlawful analysis.” In addition, existing issues such as the outdated classification of criminal offenses, ambiguity in identifying responsible actors, and disproportionately lenient sentencing standards have further endangered the effective protection of data-related legal interests. To address these emerging challenges, criminal law should evolve by expanding the scope of liability, improving legislative frameworks, enhancing regulatory coordination, and restructuring penal models. These efforts would facilitate a paradigm shift in governance from "data control" to "data utilization", aiming to reconcile the tension between technological innovation and the protection of legal interests.